PENGARUH RASIO LANCAR, RASIO UTANG PADA MODAL, PERPUTARAN TOTAL AKTIVA, DAN MARJIN LABA BERSIH TERHADAP PERUBAHAN LABA PADA PERUSAHAAN LQ-45 PERIODE 2013-2017 - Purnasari, Nina; Fransiska Turnip, Sri Sevi; Lubis, Tya Novita; Panjaitan, Sandra Angelica (EDUTECH CONSULTANT, 2019)
The purpose of this study was to determine the effect of lancer ratios, debt to capital ratios, total assets turnover, and net profit margins partially and simultaneously to changes in earnings. The population in this study were LQ-45 companies listed on the Indonesia Stock Exchange from the period 2013 to 2017, with a purposive sampling technique obtained as many as 36 companies. The data in this study are secondary data and the hypothesis testing method uses multiple linear regression analysis which produces the equation Y = 7.253-0.228LNX1 + 0.035LNX2-0.481LNX3- 0.481LNX4 The results show that partially, current ratio, total assets turnover and profit margin net has a negative and significant effect on changes in earnings, while the debt-to-equity ratio has a positive and insignificant effect on earnings changes. Simultaneously, current ratio, debt to capital ratio, total assets turnover, net profit margin have a significant effect on earnings changes.